Camel research and development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Over the past few years there has been an increasing interest in improving the productivity of camels. This is shown by the greatly increased research output, the number of conferences organized with camels as a theme, and investment in development...